Photoscopy: spectroscopic information from camera snapshots? - Schwaebel, S. Thimon; Menning, Sebastian; Bunz, Uwe H. F. (Chemical science, 2014)
The interconversion of photographic and emission spectroscopic data is described. The approach allows the collection of robust color information cheaply and quickly by photography. Photographs of arrays of emissive solutions are obtained in a fraction of a second, containing color information equivalent to that of multiple emission spectra. Critical is the extraction of the color information and comparison to emission spectra of the same array. Calibration of the camera, used as a three channel detector, is also critical. Pseudo color matching functions (not the CIE standard observer), easily measured, are the key. When using RAW data from photographs, the extracted color information (camera specific chromaticity coordinates, rg) is unique, but one-to-one correspondence with emission spectroscopic data is not achievable. The rg values are extracted from the emission spectra by multiplication of the spectra with the calibrated, camera pseudo color matching functions. The photograph/spectra relation is unique, as long as a single emission line is concerned, which is true for most practical cases.
First published: 03 Dec 2013
Gesehen am 30.10.2020